El léxico lesbofóbico: La construcción de un repertorio de odio en los ciberforos peruanos - Lovón Cueva, Carolina Mirian (2022)
The lesbophobic lexicon in Peru is created by the rejection of lesbian women because of their sexual orientation. The objectives of this paper are the following: to identify insulting lexical constructs against lesbians in Peruvian virtual forums and to interpret them as representations of symbolic violence and performative acts of hate speech. Methodologically, seven lexemes (“camionera”, “machito”, “chito”, “machorra”, “machona”, “marimacha”, “tortera”, “marimacha”) that are used in the interactions of forum members are selected. To study the semiotic signifiers and meanings, we start from the definitions proposed by academic dictionaries, particularly on Peruvianisms, and then contrast them with the social meanings situated in the discourses of the forum members; subsequently, we explain that the lexical voices generate and reproduce violence and hatred against the group of lesbian women. The article concludes that the lesbophobic repertoire perpetuates practices of symbolic violence and maintains aggressive discourses of rejection.